KHIVA KHANATE AND ITS RELATIONS WITH BRITAIN IN ARCHIVAL ANALYSIS - Jahongir Razzakov (Scholar Express Journal, 2026)
This article explores the nature, depth, and dynamics of the relations between the Khiva Khanate and Great Britain during the nineteenth century, based primarily on materials preserved in the Khiva Khanate archives and related comparative sources. By analyzing diplomatic correspondence, gift exchanges, trade records, and travel accounts, the study highlights how humanitarian considerations, political pragmatism, and regional security concerns shaped Khiva–British interactions.
Keywords: humanitarian; primarily; diplomatic correspondence; interactions